(3TQM NdGUI GdMSGHs - (3GdehShj, GdfHGWj, GdYGedj, , fhQ GdOjf, MjOQ Hf eMeO MSf, cGf MjG b (B12 (3g`s ((3GdeDdas)
(3ChdgG (B:s
... (3hGdGhdi Cfg eHfj ddaGYd haGYdg gh Gddg JYGdi hajg ZjQg ajchf GdeYfi (B... (3GdMGeOjI dg JYGdi eNJUI Hg dG jJCJj ef ZjQg JYGdi ajchf MeOG dg JYGdi HEXgGQ GdYLR Yf GdMeO acCfg bGd dG CMUj KfGA Ydjc (B...s
(3BNQgG (B:s
... (3Cf dG JfXQ Edi eG hVYJ HYjf GdMSO hdG Jehg HJehjgGJ JTHg GdQaY aj GdLSO aEf GdEfSGf eMd GdfSjGf hgPg JMaI CHjc hGdSdGe efj Ydjc hgPG HYO Cf aQZJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1\665s
(3GdPQjYI (B13 - 139( 821)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdQjGVjGJs